State Liability for Judicial Decisions Infringing EU Law – the Polish Experience - Michalak, Marcin; Dębicki, Jakub (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2022)
The liability of Member States for damages caused by the issuance of a judicial decision in breach of EU law has been shaped in the jurisprudence of the CJEU, as a mechanism to ensure effective legal protection of EU citizens. Its primary purpose is to ensure that in a situation where a court of a Member State causes damage to a citizen by violating EU laws by its ruling, the citizen has a legal remedy to obtain compensation for such a violation. Based on the principle of procedural autonomy of the Member States, such claims can be asserted on the grounds of national procedural rules under the substantive legal grounds laid down by the CJEU in its case law. Research conducted by the authors of the article indicates that despite more than 18 years of Poland’s presence in the European Union, it is extremely difficult to find rulings on liability for damages for breach of EU law by Polish courts. It seems that such a state of affairs may be caused by ambiguities and interpretative doubts that arise on the grounds of Polish procedure in the case of claims for damages for breach of EU law by the courts. Both in the doctrine and case law there are far-reaching divergences as to whether the pre-judgment provided for in the Polish Civil Code should apply to claims for breach of EU law, and if so, when it should be applied. These doubts are reflected in the scant judicial case law on the issue in question. It seems that the indicated procedural doubts and lack of clarity as to the proper procedure in pursuing such claims may deter parties from more frequent initiation of proceedings to obtain compensation for breach of EU law by a national courts in the Polish context.